2008
DOI: 10.2196/jmir.1089
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Promoting Smoking Cessation Among Methadone Users Using Multimedia Computer-Assisted Education

Abstract: Background The prevalence of smoking is very high among methadone users. As a method of delivering health education, computers can be utilized effectively. However computer-assisted education in methadone users has not been evaluated systematically. Objective This study was aimed at assessing feasibility and patient acceptance of an interactive educational module of a multi-component smoking cessation counseling computer program for former illicit drug users treated in an outpatient methadone clinic.Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Our results are supported by previous reports which demonstrated potential of interactive education about hazards of smoking [7][8]. Previous studies also showed high acceptance of mobile devices for interactive health education [9][10][11].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are supported by previous reports which demonstrated potential of interactive education about hazards of smoking [7][8]. Previous studies also showed high acceptance of mobile devices for interactive health education [9][10][11].…”
Section: Resultssupporting
confidence: 92%
“…2. Computer-assisted education on hazards of smoking in current smokers has been previously described [7]. It was shown to significantly increase smokers understanding of health risks associated with smoking.…”
Section: A the Last Systemmentioning
confidence: 99%
“…29,37,38 Patient-focused education in various topics for health care professionals and Internet-based health or wound care information for patients are also available. [39][40][41][42] Web-based information has been used to manage patients' chronic wounds via clinical practice guidelines or protocols, and via telemedicine consultations. [43][44][45][46][47][48][49][50][51] HasfieldWolfe and Rund 33 used a digital survey to assess staff development needs related to wound care, specifically malignant cutaneous wounds.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…In our previous studies we showed that interactive patient education could be successfully delivered via Internet, PDA, tablet PC and touch-screen kiosks [1][2][3][4][5][6][7][8]. In all these studies we used Computerassisted Education (CO-ED) system as an authoring platform for interactive self-paced multim d y adult learning theories [9][10][11][12][13][14][15].…”
Section: Figure 8 Quiz Question Screenmentioning
confidence: 99%